A visual language and interactive system for end-user development of internet of things ecosystems. (June 2017) - Barricelli, Barbara Rita; Valtolina, Stefano
Abstract: This paper presents the definition of a visual language and its implementation with the design of a visual interactive system for the collaborative management of Internet of Things (IoT) sensors (e.g., wearable fitness trackers, ambient sensors, fitness apps, nutrition apps, sleep trackers) for improving people's quality of life and promoting wellness awareness. The system, called SmartFit Rule Editor, is designed to be used by coaches and trainers of non-professional teams of athletes for monitoring and analyze fitness and wellness data streams and to support them in detecting relevant events and specifying rules for actions taking. Our research is framed under the scope of computer semiotics and semiotic engineering theories. This allows us to study how to support coaches and trainers as a community of domain experts – but not IT and IoT experts – to use elements of a visual language to indirectly manage physical devices and their data streams without the need to know technical specification of the devices, the apps, and the data. We apply a socio-technical approach to design being able to study the social and the technological aspects of the use of the Internet of Things ecosystem, considering them as closely interconnected and dependent. Such an approach underpins user-centered design and development methodologies in order to design the most suitable User eXperience according to users' culture, needs, context of use, and activity.